Guardian - prayer aids for visually impaired, make your pray easier .... - Samaei, Yamilah; Rifin, Zazarida; Musa, Muhammad Zamuren (2010)
Guardian device is prayer aid that designed for visually impaired or blind ppl, to perform prayer or other duties. It is because, nowadays there are many ppl that suffer from minor to variour serious vision disability which make diffeculties for those who are independance living. Most common vision problem is praying. Therefore, this device is designed to solve thoes problems. There are three function; Azan alert, Qiblat compass and electronic beards. The systems used are GPS which is well known about navigator and world clock. Moreover, digital counter systen eases you to count number of zikkrullah to be more precise and with no worry.